Spirituality of Maslahah Based Waste Management - Selamet Hartanto (AL- IKTISAB Journal of Islamic Economic Law, 2019)
The volume of waste generated by the various activities of human beings every day is always increasing. This waste becomes an urgent issue that requires special attention in handling it, especially in major cities of Indonesia. This management requires an effective and efficient method because the acceleration in this issue is very urgent. If the management is not appropriate and right on target, it will be impossible for 2020 to realize Indonesia is clean from waste. One of the things that should be done well is the management problem. Management offers that can be applied among others are the maslahah based waste management. This concept maps waste management from upstream to downstream in waste management. In this case there are several concepts to be done, including the planned behavior, understanding the community about waste, entrepreneurship, spirituality, and others. Management is certainly not only the responsibility of one party but all parties must synergize in waste management that can be a time bomb. It means if the management is not effective and efficient, then the impact will be dangerous for the survival of the community.